The Nature of Human Beings in Al Ghazali's Thought and Its Implications on Character Education - M. Fani Burhan Firmansyah; Mustopa (Yayasan Pendidikan Haiba Nasywa in cooperation with Pesantren Wahdatul Ulum Internasional, 2025)
This research aims to examine the concept of human nature in the perspective of Imam al-Ghazali's thought and its implications for character education. This research uses a qualitative approach with the method used is literature research. In al-Ghazali's view, humans consist of physical and spiritual elements. Al-Ghazali emphasizes the dominance of spiritual aspects such as qalb, spirit, aql, and nafs as the core of humanity that determines the direction of human life Character education according to Al-Ghazali not only aims to transfer knowledge, but also to form noble morals through purification of the soul (tazkiyatun nafs), spiritual approaches, and habituation of moral values from an early age. The implications of Al-Ghazali's thinking are very relevant to the goals of Indonesian national education as stated in the National Education System Law No. 20 of 2003, which emphasizes the formation of people of faith, piety, knowledge, and noble character. The contribution of this research is to provide theoretical and practical insights into the importance of integrating spiritual values in character education, so that it can be a foothold for the development of holistic education models that are in accordance with the challenges of the times. This research also shows that character education based on akhlakul karimah can be an effective solution in overcoming moral degradation among today's young generation.